Efecto del tiempo de inmersión y tipo de secado en el proceso de tunta en variedades de papas (Solanum tuberosum) ecuatorianas - Alucho Pasto, Josselin Estefanía (2022)
Tunta is a by-product of dehydrated potato (Solanum tuberosum) whose characteristic color is white and rough surface, stands out for its nutritional properties, including Resistant Starch (RA), which is important for people suffering from diabetes, cancer colon, cardiovascular diseases by acting as a prebiotic for the intestinal microflora. The objective of this research was to evaluate in Ecuadorian potato varieties the effect of immersion time and type of drying in the Tunta process, which affect the content of Resistant Starch (RA) and the amount of Calcium. An A×B×C factorial design with three, two and two levels respectively, with two replications, was used. It was determined as the best treatment based on AR at T11 (variety: Chola, immersion time: 480h, type of drying: natural), which presents a yield of 40.35%, showing an increase after applying the Tunta process. with respect to the raw material that presented a value of 6.38%. Regarding Calcium content, T3 (variety: INIAP Natividad, immersion time: 480h, type of drying: natural) was obtained as the best treatment with a value of 42.61 mgCa/100g, with an increase of 273% with regarding the raw material. The physical chemical results in the best treatment based on AR are: in ash 0.01%, moisture 18.13%, pH 5.94, crude fiber 0.05% values expressed on a dry basis, which compared to the raw material presents an increase in energy from 398.76 Kcal/100g to 412.79 Kcal/100g, on the other hand, the fat content of 0.13% is preserved. Finally, a colada-type drink was made by substituting 50% of the flour from the best Tunta treatment for oatmeal, sweetened with passion fruit jelly; to which an acceptability test was applied, presenting better results in taste and acceptability with a weighting of "good and very good", according to the hedonic scale used.